2018
DOI: 10.1093/heapro/day103
|View full text |Cite
|
Sign up to set email alerts
|

Blue care: a systematic review of blue space interventions for health and wellbeing

Abstract: There is increasing interest in the potential use of outdoor water environments, or blue space, in the promotion of human health and wellbeing. However, therapeutic nature-based practices are currently outpacing policy and the evidence base for health or wellbeing benefits of therapeutic interventions within blue space has not been systematically assessed. This systematic review aims to address the gap in understanding the impacts of blue space within existing interventions for targeted individuals. A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
285
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(294 citation statements)
references
References 80 publications
4
285
1
4
Order By: Relevance
“…After removing duplicates, 321 were manually screened, and 286 records were excluded for title and abstract. We reviewed the full text of 35 studies, 24 of which were excluded [11,12,14,18,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Finally, eleven SRs were included in the narrative synthesis ( Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…After removing duplicates, 321 were manually screened, and 286 records were excluded for title and abstract. We reviewed the full text of 35 studies, 24 of which were excluded [11,12,14,18,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Finally, eleven SRs were included in the narrative synthesis ( Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…However, the evidence for a positive association with general health, and reduced obesity, cardiovascular disease, and related outcomes, was less consistent (Gascón et al, 2017). Another review of 33 intervention studies (e.g., that used watersports among at risk communities for health and wellbeing promotion purposes) concluded that carefully structured interactions with the sea/ocean could help both personal and social wellbeing (Britton et al, 2018).…”
Section: Bathing Waters Quality and Trendsmentioning
confidence: 99%
“…Two recent systematic reviews highlight the benefits of blue space in improving mental health, especially wellbeing ( Britton et al 2019 ), and the advantages of access to green space for children, which is associated with improved mental wellbeing, overall health and cognitive development of children ( McCormick 2017 ). In 2017, the Architectural Design journal also 4 published a number of case studies related to the benefits of nature for patients and healthcare professionals.…”
Section: Naturementioning
confidence: 99%